Pengembangan Media Pembelajaran Animasi Berbasis Animaker dalam Struktur Teks Negosiasi Siswa Kelas X SMA Swasta Nurul Islam Indonesia Medan - Meidiana Batubara; Deliani; Nila Safina; Ratna Soraya (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aimed to describe the development process and feasibility of animation learning media based on animaker in class X SMA Nurul Islam Indonesia Medan. The source of data is a questionnaire. The data collection techniques used observation and interviews to gain data in learning the structure of negotiating texts. This study used research and development (R&D) by Thiagajaran that consists of 4 stages of development; 1)definition stage, 2)design stage, 3)development and 4)dissemination. The researchers tested the product in large and small groups. The material expert validation of the developed animaker-based animation learning media obtained an overall average as 78% or "Satisfaction", means that the product is eligible to be tested. While media experts obtained an overall average as 98% or "Very Satisfaction" means that the product deserves to be tested into large and small groups. The results of the small group test in class X IPA obtained 90% and the small group test in class X IPS obtained 80%. Then for the results of the percentage of student response questionnaires in the form of large group tests, in class X IPA it was obtained 94% and in class X IPS it was obtained 90%. From all the percentages obtained for the developed learning media, the learning media is declared to be effectively used in learning in class X science